Long-Term Changes in Hepatic Fibrosis following Hepatitis C Viral Clearance in Patients with and without HIV. Issue 6 (August 2019) - Balmaceda, Julia B; Aepfelbacher, Julia; Belliveau, Olivia; Chaudhury, Chloe S; Chairez, Cheryl; McLaughlin, Mary; Silk, Rachel; Gross, Chloe; Kattakuzhy, Sarah; Rosenthal, Elana; Kottilil, Shyam; Kleiner, David E; et al.
Background: While acute changes in hepatic fibrosis are recognized shortly after achieving sustained virological response (SVR) using direct-acting antiviral therapies, long-term outcomes for the growing population of successfully treated patients with HCV remain uncertain. The aim of this study is to characterize long-term changes in fibrosis following SVR in patients with and without HIV and to identify potential factors associated with progression or regression of fibrosis. Methods: We completed a prospective longitudinal study of 162 subjects with HCV (34% HIV-coinfected) with pre-treatment fibrosis stage determined by liver biopsy and post-SVR transient elastography. Progression of fibrosis was defined as a two-stage or greater increase in fibrosis, while regression was defined as a two-stage or greater decrease at last follow-up. The median duration of follow-up was 4.1 years. Results: Fibrosis progression occurred in 4% of subjects while regression occurred in 7% and 89% were stable and did not differ by HIV coinfection. Fibrosis progression was associated with increased body mass index (BMI), hepatic steatosis and smoking pack-years. In a multivariable logistic regression, HIV coinfection ( P =0.009), lower steatosis score ( P <0.05) and lower smoking pack-years ( P =0.0007) were associated with a lower fibrosis score at last follow-up. Conclusions: We identify potentially important relationships between BMI, hepatic steatosis and smoking, and changes in hepatic fibrosis post-SVR in patients with and without HIV coinfection. Attention to modifiable risk factors such as body weight and smoking may reduce the risk of liver disease progression in the growing population of successfully treated chronic HCV patients.